Inhalable Solubilized Zileuton for Improved Lung Targeting in vitro and in vivo Analysis - Asif, Afzal Haq; Meravanige, Girish; Nagaraja, Sreeharsha; Shariff, Arshia; Thimmasetty, Juturu; Narayana, Kavitha Arenur (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Pulmonary diseases that affect the normal functioning of the lungs show airway symptoms ranging from change in airflow to bronchiectasis. Zileuton is an inhibitor of 5-lipoxygenase enzyme that catalyzes the synthesis of leukotrienes. Zileuton is used in the management of inflammatory conditions of the upper airways like obstructive pulmonary conditions and acute lung inflammation. Although a promising therapeutic, zileuton is poorly water-soluble and requires frequent administration to overcome bioavailability issues and maintain therapeutic levels that often lead to adverse reactions, especially to the non-targeted organs. Materials and Methods: Therefore, we designed a rapidly nanoemulsifying formulation of zileuton using Acrysol K150 as an oil, Cremophor EL as a surfactant, and Transcutol HP as a cosolvent. Results: This self-emulsifying composition exhibited showed a mean globule size of 133 ± 3.6 nm with a polydispersity index of 0.38. Scanning electron microscopy (SEM) images revealed the spherical shape of emulsion globules. In vitro lung deposition showed >80% delivery to the deep lung tissue. Mass median aerodynamic diameter of 2.05±0.98 μm for the aerosolized formulation. In vivo, pharmacokinetic studies in Wistar rats by inhalation route showed that the zileuton-loaded nanoemulsifying formulation had a significantly higher concentration in the lung compared to other non-target organs. The in vivo efficacy in the lipopolysaccharide-induced acute lung inflammation model in rats significantly impeded the protein accumulation and neutrophil infiltration in the lungs. Conclusion: The zileuton-loaded nanoemulsifying inhalable formulation successfully improved the therapeutic efficacy of zileuton specifically to the lung thereby minimizing the off-target organ side effects.
Keywords: Self-emulsifying; Zileuton; Aerosols; Pharmacodynamics; in vivo; Lung targeting